Cross-amplification of Y chromosome-specific markers isolated from horse (Equus caballus) in Malayan tapir (Tapirus indicus) - Tan, Y. L.; Annavi, Geetha (Department of Biology, Faculty of Science, Universiti Putra Malaysia, 2016)
This study was conducted to evaluate the cross-amplification of six Y chromosome-specific markers that were isolated from horse (Equus caballus) in Malayan tapir (Tapirus indicus). All the six markers failed to yield positive results in Malayan tapirs with no amplification (Eca.YM2), and with amplification of single band (Eca.YP9) or multiple bands (Eca.YJ10, Eca.YH12, Eca.YE1 and Eca.YA16) in both male and female individuals. Twelve faecal samples were collected from five male individuals of Malayan tapir and stored in three different storage methods (frozen, DET and 80% ethanol). DNA was extracted using a modified protocol of Zhang et al. (2015), yielded DNA concentrations that were not statistically different among the three storage methods based on one-way ANOVA test. Scoring of molecular markers was not carried out because none of the six markers gave a positive result and therefore this step was discontinued.